Learning from “Totto-chan: the Little Girl at the Window”: An Educational Perspective from Japanese Author - Sadhya Permeiswari (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2019)
The novel “Totto-chan: The Little Girl at the Window” is a novel which some parts of its story reflects concept of education that is unique and different. The concept education in this novel related with educational value according to Moleong perspective. Therefore, this research is mainly purposed to search about what are the educational values found in Tottochan: The Little Girl at the Window”? and how educational values appear in “Tottochan: The Little Girl at the Window” based on Moleong perspective. This research is qualitative one by using content analysis method. Two data sources were chosen the primary data source is the novel itself and the secondary data are books, literature, official websites and other relevant materials. In general, the result found educational values contained in the novel based on Moleong perspective. By this research, it is expected that teachers can implement the positive things that exist in this study and in the novels at school and also encourage students’ interest in literature.